An exploration of service quality in relation to tourist satisfaction at Lebakmuncang Tourism Village - Anggani, Mayang Fitri; Maemunah, Ita; Saepudin, Pudin (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: This study aims to explore the relationship between service quality and tourist satisfaction in Lebakmuncang Tourism Village, located in Bandung Regency. The research emphasizes the importance of service quality in enhancing visitor satisfaction, particularly within the framework of community-based tourism. Research Methodology: A descriptive quantitative approach was used in this study. Data were collected from 95 tourist respondents through a structured questionnaire utilizing the Likert scale. The instrument was adapted from the SERVQUAL model and included additional dimensions such as willingness to serve, openness, reputation, and credibility. Results: The results indicate that tourists provided highly positive evaluations of various service quality dimensions, including physical evidence, reliability, responsiveness, assurance, empathy, and emotional aspects. These assessments correspond with high levels of tourist satisfaction in terms of contentment, enjoyment, favorable impressions, and overall experience. Conclusion: The study confirms a strong correlation between service quality and tourist satisfaction. Quality service not only boosts visitor loyalty and destination appeal but also supports operational efficiency through positive word-of-mouth. Limitations: This study is limited to a single destination and uses self-reported data, which may not capture broader variations or longitudinal changes in perception. Contributions: This research contributes empirical evidence to the tourism service literature and offers strategic insights for stakeholders in community-based tourism to enhance service delivery and destination sustainability.